1999
DOI: 10.1089/neu.1999.16.243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Six Weeks of Chronic Ethanol Administration on the Behavioral Outcome of Rats After Lateral Fluid Percussion Brain Injury

Abstract: This study examined the effects of 6 weeks of chronic ethanol administration on the behavioral outcome in rats after lateral fluid percussion (FP) brain injury. Rats were given either an ethanol liquid diet (ethanol diet-groups) or a pair-fed isocaloric sucrose control diet (control diet groups) for 6 weeks. After 6 weeks, the ethanol diet was discontinued for the ethanol diet rats and they were then given the control sucrose diet for 2 days. During those 2 days, the rats were trained to perform a beam-walking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Furthermore, CEAn of 6 weeks without any intoxication at the time of brain injury also did not affect the injury-induced cognitive impairment (Zhang et al, 1999). Because cognitive dysfunction is a major disability in surviving TBI patients and the majority of TBI patients had both chronic ethanol abuse and acute intoxication, this study examined the effects of 3 months of CEAn accompanied by intoxication (at the time of injury) on the cognitive and morphologic outcome of lateral fluid percussion (FP) brain injury in the rat.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…Furthermore, CEAn of 6 weeks without any intoxication at the time of brain injury also did not affect the injury-induced cognitive impairment (Zhang et al, 1999). Because cognitive dysfunction is a major disability in surviving TBI patients and the majority of TBI patients had both chronic ethanol abuse and acute intoxication, this study examined the effects of 3 months of CEAn accompanied by intoxication (at the time of injury) on the cognitive and morphologic outcome of lateral fluid percussion (FP) brain injury in the rat.…”
mentioning
confidence: 80%
“…Ethanol administration of about 6 weeks did not affect certain aspects of the neurochemical outcome (Prasad et al, 1997) or the neurologic motor deficits (Shapira et al, 1997;Zhang et al, 1999) associated with TBI in rats.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Some laboratory studies, using a variety of TBI models and species, have found increased mortality, worse neuropathology, and worse neurological outcome in ethanol-treated animals (Albin and Bunegin, 1986;Flamm et al, 1977;Franco et al, 1988;Shapira et al, 1997). Other TBI studies have not demonstrated a deleterious effect of ethanol in TBI (Masse et al, 2000;Zhang et al, 1999) while one study suggests a possible neuroprotective effect (Kelly et al, 1997). In previous studies from our laboratory, which utilized a porcine fluid percussion model, we found early respiratory depression, decreased cerebral perfusion pressure (CPP), and decreased cerebral blood flow (CBF) in ethanol-treated animals (Zink and Feustel, 1995;Zink et al, 1993).…”
mentioning
confidence: 99%